(untitled) (General Practice, 2022)
Introduction. From March 14th to May 04th, 2022, there had been a call center in the Town Hall of Novog Sada (further call center). There were four general physicians (GPs) from Primary Healthcare Center “Novi Sad” on-call, and they gave information and answers to the questions asked by the citizens about the COVID-19 pandemic. Objective. We aimed at presenting the structure of the questions we asked on-call GPs in the call center. Method. Retrospective analysis of the phone calls, on one phone line, in one seven-hour shift, during 36 working days. Results and discussion: We analyzed 757 questions, classified into 14 call categories: 1. Fever and health issues that might be connected to COVID-19, 165 (21,80%). 2. Health issues not connected to COVID-19, 134 (17,70%). 3. Social problems that occurred after the going out ban for those over 65, and curfew, 68 (8,98%). 4. Isolation measures, 67 (8,85%). 5. Going to follow up health checks, 61 (8,06%). 6. Problems buying food and drugs, 46 (6,08%). 7. Going out ban, 44 (5,81%). 8. Buying and using PPE and disinfectants, 20 (2,64% ) 9. Testing, 12 (1,59%). 10. Going or rather not going to work, 11 (1,45%). 11. Psychological problems, 9 (1,19%). 12. Complaints of work organizations, 6 (0,79%). 13. Questions that couldn`t be cataloged in any of the previously mentioned categories, 89 (11,76%). 14. Calls from other counties, 25 (3,30%), which was interesting. Conclusion: In the early phase of the pandemic oncall GPs helped citizens solve different problems, even nonhealth ones. They remained the first line of contact with the health system, showing that primary health care, as a part of the health system, is always available. Keywords: COVID-19 pandemic, call center, organization, primary healthcare